EFFECTIVE COMMUNICATION AS THE KEY TO SUCCESSFUL DISTANCE EDUCATION - Indah Sulistiani; Syarifuddin Syarifuddin; Silvia Ekasari (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study is to analyze effective communication strategies used in distance education and their impact on the success of the learning process. The research method in this study used literature. The results of the literature review revealed that two-way communication between educators and students supports a more dynamic and interactive learning environment, which increases students' understanding of the material and motivation. The importance of educators providing timely and relevant feedback is a key factor in improving students' abilities as well as providing emotional support. Educator training in the use of digital communication tools is recognized as a prerequisite for the implementation of effective communication strategies. The study concludes that the development of educators' digital competencies and the availability of adequate technological resources are factors that support the achievement of communication effectiveness in distance education. Implications for educational practice include recommendations for the development of educator training programs, the integration of communication tools in learning platforms, and the formulation of policies that support the use of technologies that are innovative and responsive to student needs.